2010
DOI: 10.1103/physrevlett.105.086102
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Ice: Nanowire Regelation

Abstract: Even below its normal melting temperature, ice melts when subjected to high pressure and refreezes once the pressure is lifted. A classic demonstration of this regelation phenomenon is the passing of a thin wire through a block of ice when sufficient force is exerted. Here we present a molecular-dynamics study of a nanowire cutting through ice to unravel the molecular level mechanisms responsible for regelation. In particular, we show that the transition from a stationary to a moving wire due to increased driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…However, in the absence of a magnetic field their selforganization is governed by the hard-sphere repulsion between the particles and a combination of electrostatic repulsion due to their charged surfaces and van der Waals attraction between them leading to the formation of a RHCP structure. Our findings are in good agreement with simulation results [39,40] on the assembly of these particles. However, our experimental study is remarkably different from that of simulation in one respect.…”
Section: Angewandte Chemiesupporting
confidence: 92%
See 1 more Smart Citation
“…However, in the absence of a magnetic field their selforganization is governed by the hard-sphere repulsion between the particles and a combination of electrostatic repulsion due to their charged surfaces and van der Waals attraction between them leading to the formation of a RHCP structure. Our findings are in good agreement with simulation results [39,40] on the assembly of these particles. However, our experimental study is remarkably different from that of simulation in one respect.…”
Section: Angewandte Chemiesupporting
confidence: 92%
“…Simulations, that have tried to address these questions, predict an assortment of equilibrium phases such as the body-centered tetragonal (BCT) and face-centered cubic (FCC) phases that can coexist with the 1D particle chains. [37][38][39][40] Experimentally it has been shown that in the presence of a magnetic field these nanoparticles self-assemble to a 1D chain phase. With an increase of both the strength and the gradient of the applied magnetic field [29,[41][42][43] these chains evolve into 2D sheets and 3D structures.…”
mentioning
confidence: 99%
“…It has recently been used to study regelation, i.e., the melting of ice when subjected to high pressure and its refreezing once this pressure is lifted. 34 Here, we embed nonpolar solutes within 3DMB water and use Monte Carlo simulations to study structural and thermodynamic properties of these systems. Previous studies using the two-dimensional Mercedes-Benz model have shown that this method provides valuable information about the hydrophobic effect and its thermodynamics in the presence of small molecules and the denaturation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…When these interactions are strong enough to overcome the Brownian motion, particles initially form dipolar chains, which then laterally coalesce to form the lowest energy structures such as a body-centered tetragonal, hexagonally close-packed (HCP), or face-centered cubic (FCC) lattice depending on the particle concentration and field. [32][33][34] Figure 1f demonstrates the assembly of micrometer-sized latex particles into 2D crystalline arrays upon the application of an AC electric field using coplanar electrodes. [33] It uses dielectrophoresis (DEP, i.e., the movement of polarized particles along a field gradient) and the induced particle interactions to cause the self-assembly of colloidal particles into HCP arrays.…”
Section: Self-assembly For Nanomanufacturingmentioning
confidence: 99%